Parenting Patterns Towards Adolescents Who Are Victims of "Inhalant Abuse" Addiction In Biring Romang Village, Manggala Subdistrict, Makassar City - Said, Irwanti; Muqniati, Muqniati (Jurnal Indonesia Sosial Sains, 2026)
This research examines the parenting patterns of parents towards adolescents who are victims of glue addiction in Biring Romang Village, Manggala Subdistrict, Makassar City. The phenomenon of inhalant addiction among adolescents is a complex social problem influenced by family, environmental, and psychological factors. This study aims to (1) identify the factors causing adolescents to engage in glue-sniffing behavior, (2) analyze the parenting patterns of parents towards adolescents who are victims of glue addiction, and (3) examine the obstacles faced by parents in dealing with these adolescents. This study uses a qualitative approach with a guidance and counseling perspective, collecting data based on social facts in the field, which are then analyzed descriptively and from which conclusions are drawn inductively. The results of this study indicate that a patient and attentive parenting style with open communication plays a significant role in influencing behavioral changes in adolescents addicted to glue. Adolescents tend to respond positively to a non-repressive parental approach and can build positive emotional relationships. Meanwhile, parents face obstacles such as limited control, negative environmental influences, and social stigma from the community. The implications of this study emphasize the importance of parents' role in maintaining the continuity of positive parenting patterns, the need for social awareness in the community to accept and support adolescents addicted to glue, and the urgency of establishing youth communities at the subdistrict or neighborhood level as a forum for developing adolescent talents and interests.